Billboard art as a temporary autonomous zone:urban art’s exhibitive platforms and pirate speeches (Palíndromo, 2018)
Advertising stands for a group of practices that ally discursive techniques with symbolic constructions to brand development and uses media to sell its objects. From the work of art analysis of Félix Gonzalez-Torres, Barbara Kruger, PORO colective e ETC colective, it is asked: can contemporary art enable a counterattack to normative speeches, proposing the occupation of billboards as an exhibitive platform for pirate concepts? From this initial question, this arcticle’s main goal is to correlate the billboard media as a tool of capitalist rhetoric and its occupation as an exhibitive platform for pirate speeches. Realizing urban art as a polemizer of speeches on urban iconography, it is concluded that billboard art builds spaces-between because are as polemic as ephemeral, making possible poetics to the city’s urbanized space, a voice attempt within an excess of urban voices.
Keywords: temporary autonomous zone; billboard art; poetic terrorism; urban art; consumerism languages